2012
DOI: 10.1007/s00253-012-4528-8
|View full text |Cite
|
Sign up to set email alerts
|

Ectoine-mediated protection of enzyme from the effect of pH and temperature stress: a study using Bacillus halodurans xylanase as a model

Abstract: Compatible solutes are small, soluble organic compounds that have the ability to stabilise proteins against various stress conditions. In this study, the protective effect of ectoines against pH stress is examined using a recombinant xylanase from Bacillus halodurans as a model. Ectoines improved the enzyme stability at low (4.5 and 5.0) and high pH (11 and 12); stabilisation effect of hydroxyectoine was superior to that of ectoine and trehalose. In the presence of hydroxyectoine, residual activity (after 10 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 33 publications
3
18
0
1
Order By: Relevance
“…For example, we found that KOs encoding synthesis of the osmoprotectant ectoine ( K06718 and K06720 ) were correlated with pH but not salinity optima ( Table 3 ). Recent work suggests that ectoine may have a role in stabilizing enzymes at extreme pH values ( 49 ). Our result indicates that pH homeostasis may be another role for ectoine in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we found that KOs encoding synthesis of the osmoprotectant ectoine ( K06718 and K06720 ) were correlated with pH but not salinity optima ( Table 3 ). Recent work suggests that ectoine may have a role in stabilizing enzymes at extreme pH values ( 49 ). Our result indicates that pH homeostasis may be another role for ectoine in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Since hydroxyectoine often possess function-preserving and stress-relieving properties superior to those of ectoine [29], [35][38], one wonders why not all ectoine producers synthesize 5-hydroxyectoine since this can readily be accomplished from ectoine in a single step [20]. Part of the answer to this question becomes apparent when one considers the physiological requirements and the oxygen dependence of the ectoine/hydroxyectoine producer microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their closely related chemical structures, 5-hydroxyectoine often possesses superior stress protecting and function preserving properties than its precursor molecule ectoine [29], [35][38]. Here, we focus on the ectoine hydroxylase, the enzyme that forms (4 S ,5 S )-2-methyl-5-hydroxy-1,4,5,6-tetrahydropyrimidine-4-carboxylic acid from the precursor ectoine through a region-selective and stereospecific hydroxylation reaction [13], [20].…”
Section: Introductionmentioning
confidence: 99%
“…The very high salinity used to cultivate the ectoine/hydroxyectoine producer organism H. elongata in the established industrial production process is harsh on the fermentation and downstream processing equipment (32). Therefore, there has been considerable interest in developing alternative fermentation processes (54,55), in exploiting additional natural ectoine/hydroxyectoine producers (56, 57) (including a bacterium that secrets them naturally into the medium [58]), and in engineering natural and synthetic microbial production hosts for enhanced recovery of these high-value compounds (1,32). With respect to the latter approaches, ectoine/hydroxyectoine biosynthetic genes have been cloned into plasmids under the transcriptional control of either natural ect or synthetic promoters and transferred to Escherichia coli or Corynebacterium glutamicum host strains (59)(60)(61)(62) or integrated into the chromosomes of biotechnological workhorses such as C. glutamicum (63) or the methylotrophic yeast Hansenula polymorpha (64).…”
mentioning
confidence: 99%